Implementing Artificial Intelligence Algorithms For Decision-Making In Autonomous Packaging Processes Of Robotic Manipulators - Sh.S.Djurayev; M.M.Abdumajidova; D.M.Nabijonov (Genius Journals, 2025)
The increasing demand for flexible, adaptive, and efficient packaging systems in modern manufacturing has led to the integration of artificial intelligence (AI) in robotic manipulators. This paper presents a detailed study on the implementation of AI-based decision-making systems to enhance the autonomy of packaging robots. By utilizing a hybrid approach combining neural networks (NN) and fuzzy logic (FL), the system is capable of real-time learning and adaptation to dynamic packaging environments. Experimental evaluations reveal substantial improvements in throughput, reduction in error rates, and decreased energy consumption compared to conventional systems. The results highlight the potential of AI algorithms to revolutionize the packaging industry and contribute to the advancement of Industry 4.0.
Keywords: Robotic Manipulator; Autonomous Packaging; Neural Networks